PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DENGAN PERSEPSI DUKUNGAN ORGANISASIONAL SEBAGAI VARIABEL MODERASI - Megawati Megawati; Nurul Syahna (Jurnal Manajemen Inovasi, 2018)
Thisaim wastoinvestigateweatherjobsatisfactionenchancesorganizationalcommitmentamong nursingpersonelwhile exploringwhether organizationalsupport perceptionhasamoderatingeffectonthe relationshipbetweenjobsatisfactionand organizationalcommitment.Asurvey wassentto111nursesatRumahSakitIbudanAnak (RSIA)PemerintahAceh.Accordingtotheresearchfindings,nurses’jobsatisfactionhasa positive andsignificantinfluence onorganizationalcommitment.Furthermore theresults showed thatorganizational supportperception brings impact forward organizational commitment. Result alsoindicated that themoderating effect ofnurses’ organizational supportperceptionwas weakwiththevalue0,214.Thisstudysuggest thatorganizational supportperceptionwill developasenseofbelonging.Thiskindofrelationshipisrarely discussedintheresearchliterature,anditcanbeappliedforhumanresourcesmanagement of nursing staff atRumahSakitIbu dan Anak(RSIA)Pemerintah Aceh.  Keyword: OrganizationalSupport, JobSatisfaction, Organizational Commitment, Moderating Effect, NursingStaff